Fusion imaging to evaluate the radiographic anatomical relationship between primary tumors and local recurrences in retroperitoneal soft tissue sarcoma - Weigl, Helene; Janssen, Sonja; Vassos, Nikolaos; Hohenberger, Peter; Simeonova-Chergou, Anna; Wenz, Frederik; Haubenreisser, Holger; Jakob, Jens (Surgical oncology, 2020)
Background - Local recurrence (LR) of retroperitoneal soft tissue sarcoma (RPS) is a common and life-threatening event. The evaluation of the exact anatomical patterns of local recurrence might help to improve local treatment in RPS. - Methods - Of our local database we extracted ten patients with LR of RPS with axial MRI and/or CT datasets of the primary tumor (PT) and the LR. Using the Osirix DICOM viewer Version v.3.9.4 64-bit (Pixmeo, Geneva, Switzerland) we performed a three-step fusion algorithm consisting of: a) 3-point co-registration of the axial datasets depicting the PT and the LR using three abdominal landmarks b) re-orientation of the datasets and c) image fusion. We evaluated the feasibility of this technique with regard to categorizing the localization of LR as within or distant from the PT. - Results - Fusion imaging was feasible in seven out of ten patients. In the other three patients anatomical shifting of organs after surgery led to a relevant mismatch of anatomical landmarks and impeded interpretation of the fused images. In five of seven patients with successful fusion imaging, local recurrences were located within the anatomical borders of the primary tumor, in two out of seven patients local recurrences were distant to the primary. - Conclusions - Fusion imaging of primary tumors and local recurrences is feasible in most patients with RPS. Most local recurrences occurred within the anatomical localization of the primary tumor. For further investigations validation of the technique in larger patient cohorts is required.
Gesehen am 15.12.2025